Les jeux d’eau du parc de Saint-Cloud. Des premières créations à la magnificence du parc mise en scène par Étienne Allegrain - Solveig d’Aboville (Les Cahiers de l'École du Louvre)
Located in a particularly favourable location for its development, the Parc de Saint-Cloud has both superb views and a topography and geology conducive to the creation of water features. Taking advantage of these advantages, the successive owners of the château have created many water features since the late sixteenth century, each wishing to make the park a reflection of their taste and their social success, whether real or projected. In the late seventeenth century, the younger brother of Louis XIV, Philippe d’Orléans, continued this dynamic, but on a much larger scale, making gushing water the main spring of garden design, taking advantage of both its decorative character and its capacity to symbolise the owner’s power. Faced with numerous constraints linked to the uneven topography and the presence of pre-existing facilities, he adapted the function, layout and ornamentation of his gardens to this environment.